The mircrine mechanism controlling cardiac stem cell fate - Hosoda, Toru (Frontiers in Genetics, 2013)
The recent identification of c-kit-positive cardiac stem cells revealed the great growth reserve of the heart, in which connection among cells might be essential in regulating their fate. Especially, the mircrine mechanism, translocation of microRNAs (miRs) from a cell to another via gap junctions, appeared to be important in controlling the differentiation of cardiac stem cells. The modification on miR expression and/or translocation may be able to enhance further the clinical efficacy of cellular therapy.